Parents as people. Problematising parental involvement programmes. - Lyn Tett (Adult Education Research Conference, 1999)
This paper describes four case studies of parental involvement programmes and examines: the factors that enable partners to collaborate effectively; how the role of 'parent' is constructed; the contribution that education can make to combating social exclusion.